Evaluación de irradiancia de las lámparas de fotocurado de luz LED y halógena de las clínicas odontológicas de la universidad Antonio Nariño sede Armenia (2021)
The dental clinics of the University Antonio Nariño (UAN), Armenia campus, are a space for the preparation of future professionals, these have the necessary equipment to perform various procedures that aim to provide the necessary skills for the work of the dentist. The aim of this project was to evaluate the irradiance levels of the eleven light curing units (LCU) the which are found in the mentioned clinics. Information obtained from several sources was compiled where determining factors were mentioned to obtain a successful photopolymerization of the materials, among which the level of irradiance delivered by the LCUs stood out. The results shown by the devices in the measurement were then compared with the reports in the literature that talk about a minimum level of irradiance recommended to avoid possible failures in the restorations in the short, medium and long term as much as possible. Of the eight sources that spoke about a minimum accepted irradiance, five determined the 300 mW/cm2 and three the 400 mW/cm2. Of the eleven LCUs evaluated, one did not comply the first rank, while four LCUs did not comply the second range.